2015
DOI: 10.3727/096368914x684033
|View full text |Cite
|
Sign up to set email alerts
|

Human Amniotic Membrane-Derived Mesenchymal and Epithelial Cells Exert Different Effects on Monocyte-Derived Dendritic Cell Differentiation and Function

Abstract: We previously demonstrated that mesenchymal cells from human amniotic membrane (hAMTCs) inhibit the generation and maturation of monocyte-derived dendritic cells (DCs) in vitro. Considering the crucial role of DCs in the immune response and that epithelial cells of the human amniotic membrane (hAECs) share some of the immunoregulatory properties of hAMTCs, we investigated whether hAECs also modulate monocytederived DCs. We compared hAECs with hAMTCs in a cell-to-cell contact setting and their secreted factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
111
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 92 publications
(115 citation statements)
references
References 80 publications
(113 reference statements)
4
111
0
Order By: Relevance
“…Moreover, Pro-inflammatory cytokines including IL-1a and IL-1b are also down regulated by the AM [13]. In addition, both amniotic epithelial and mesenchymal cells have the ability to down-regulate the expression of TNF-a in monocyte-derived dendritic cells [58]. Therefore, the AM could inhibit coagulation by inhibiting inflammation.…”
Section: Evidencementioning
confidence: 97%
“…Moreover, Pro-inflammatory cytokines including IL-1a and IL-1b are also down regulated by the AM [13]. In addition, both amniotic epithelial and mesenchymal cells have the ability to down-regulate the expression of TNF-a in monocyte-derived dendritic cells [58]. Therefore, the AM could inhibit coagulation by inhibiting inflammation.…”
Section: Evidencementioning
confidence: 97%
“…One of the hallmark properties of placental MSC is their immune modulatory ability [9,11,12,33,34]. In fact, the use of placental MSC has proven beneficial in preclinical models of diseases with underlying altered inflammatory processes [11,17], altogether rendering these cells attractive therapeutic options.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the monocyte-macrophage compartment is also influenced by hAMSC. Specifically, we have recently demonstrated that hAMSC block monocyte differentiation towards dendritic cells and induce their macrophage differentiation [12]. MSC isolated from placental villi exert similar immune modulatory effects both versus T cells [13] and monocytes [14].…”
Section: Introductionmentioning
confidence: 99%
“…hAEC were isolated from term placentas ( n = 5) as previously described . Briefly, the amnion was detached from chorion and washed in PBS (Sigma‐Aldrich, St Louis, MO, USA) supplemented with 100 U/ml penicillin (Lonza, Basel, Switzerland) and 100 μg/ml streptomycin (Sigma‐Aldrich).…”
Section: Methodsmentioning
confidence: 99%
“…Animal experiments were carried out in accordance with the guidelines established by the Italian law DL 26/2014 on the accommodation and care of animals used for scientific purposes. The hAEC isolation hAEC were isolated from term placentas (n = 5) as previously described [24]. Briefly, the amnion was detached from chorion and washed in PBS (Sigma-Aldrich, St Louis, MO, USA) supplemented with 100 U/ml penicillin (Lonza, Basel, Switzerland) and 100 lg/ml streptomycin (Sigma-Aldrich).…”
Section: Ethics Statementsmentioning
confidence: 99%